Quality switchingvs assessment platform-matched implants of systematic reviews an overview on platform - Santiago, Joel Ferreira; Lemos, Cleidiel Aparecido Araújo [UNESP]; de Luna Gomes, Jéssica Marcela [UNESP]; Verri, Fellippo Ramos [UNESP]; Moraes, Sandra Lucia Dantas; Pellizzer, Eduardo Piza [UNESP] (American Academy of Implant Dentistry, 2020)
The objective of this study was to perform a quality analysis of systematic reviews with meta-analyses that focused on the comparison of platform-switching (implant-abutment mismatching) and platform-matched (PM) implants. The assessment of multiple systematic reviews (AMSTAR) and Glenny (Checklist) Scales were used to qualify the studies. PubMed, Scientific Electronic Library Online (SciELO), Web of Science (formerly ISI Web of Knowledge), and Cochrane databases were searched, by topic, for systematic reviews on dental implants with switching platforms. A total of 8 systematic reviews, including 7 studies with meta-analyses, were selected. The AMSTAR scale indicated a high (n ¼ 6) to moderate (n ¼ 2) score for the included studies. The quantitative analysis indicated that platform-switching implants preserved more bone tissue when compared with platform-matched implants (6 meta-analyses; P, .001, smaller mean difference: -0.29 mm, 95% CI: -0.38, -0.19 and greater mean difference: -0.49 mm, 95% CI: -0.73, -0.26). Quantitative analysis based on 7 systematic reviews with meta-analysis indicated positive peri-implant bone preservation for implants restored with an implant-abutment mismatching (PSW). Further, there is evidence to improve the design of current systematic reviews. Future systematic reviews in this thematic area should consider searches in gray literature and different databases and include only randomized controlled clinical studies.
Keywords: Data pooling; Dental implant abutment design; Meta-analysis as topic; Review